2018
DOI: 10.3389/fimmu.2018.02583
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr Virus-Associated T-Cell Lymphoproliferative Disorder Presenting as Chronic Diarrhea and Intestinal Bleeding: A Case Report

Abstract: Systemic Epstein-Barr virus-positive T-cell lymphoproliferative childhood disease (EBV+ T-LPD) is extremely rare. Primary acute or chronic active Epstein-Barr virus infection triggers EBV+ T-LPD's onset and the disease involves clonal proliferation of infected T-cells with activated cytotoxic phenotype. The adult-onset EBV+ T-LPD (ASEBV+ T-LPD) is even rarer and needs to be extensively studied. Further, according to literature review, it is a challenge to find patients who are immunocompetent and diagnosed wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 18 publications
1
14
0
1
Order By: Relevance
“…Indolent GI T-LPD cases may rarely be associated with EBV infections. Wang et al has recently reported a very rare case of adult-onset, immunocompetent EBV + GI T-LPD (8). This case was a middle-aged woman with chronic diarrhea and severe intestinal bleeding.…”
Section: Case Reportsmentioning
confidence: 94%
“…Indolent GI T-LPD cases may rarely be associated with EBV infections. Wang et al has recently reported a very rare case of adult-onset, immunocompetent EBV + GI T-LPD (8). This case was a middle-aged woman with chronic diarrhea and severe intestinal bleeding.…”
Section: Case Reportsmentioning
confidence: 94%
“…EBV infects about 95% of human beings worldwide, although most of them are asymptomatic. 5 However, it is involved in the pathogenesis of lymphoma and HLH. The latter is a rare but life-threatening disease characterized by uncontrolled hyperinflammation and subsequent systemic organ failure.…”
Section: Gastric Ulcer As the Main Complication In Hemophagocytic Lymmentioning
confidence: 99%
“…3 While gastrointestinal involvement is relatively uncommon (18%), and mostly occurs in the intestine. 5 patients with permanent remission, but it can be done only when the patient's condition is stable. 5,8 In conclusion, we described here a patient initially diagnosed as gastric ulcers, but finally identified as having HLH with EBV infection.…”
Section: Gastric Ulcer As the Main Complication In Hemophagocytic Lymmentioning
confidence: 99%
“…Chronic active Epstein-Barr virus infection (CAEBV) is a systemic EBV-positive lymphoproliferative disorder (EBV-LPD), which is marked by persistent infectious mononucleosis-like symptoms. CAEBV may result in life-threatening complications [16] such as malignant lymphomashepatic failure, interstitial pneumonia, coronary artery aneurysms, central nervous system (CNS) involvement, hemophagocytic syndromes and massive hemorrhage from the gastrointestinal tract. However, it is very rare for a patient to have several synchronous symptoms owing to EBV infection.…”
Section: Introductionmentioning
confidence: 99%